Multifocal Arterial Thrombosis during Thalidomide Therapy: Case Report and Review of the Literature - Monica Ferri; Gianluca Faggioli; Francesca Fratesi; Andrea Stella (Case Reports in Medicine)
Introduction. Thalidomide has been associated with both venous and arterial thrombotic events. Case Presentation. A 66-years old man during thalidomide therapy for myeloma experienced acute right arm ischemia, emergently treated with thrombectomy and, on postoperative day one left side weakness with right internal carotid thrombosis. Discussion. Because of the increased risk of arterial thrombosis complication, prophylactic therapy with ASA or anticoagulation during thalidomide administration is mandatory.